Creative works as one of the solution to the recycle campaign / Muhammad Hilmi Jaafar - Jaafar, Muhammad Hilmi (2015)
Every day we will produce trash, trash or the remaining solids that are not in use and no longer needed. Trash consists of solids, liquids and gas. To reduce the amount of waste is produced by the community, one of the steps that should be in practiced is recycle. There are several types of trash material or waste that was generated by we can be generated as stuff or just the same stuff with re-processing the stuff Recycle can save the environment from pollution that is not in desire, trash disposal according to category can help the environment. In Malaysia there are various government agencies and non government that support program that related to recycle. The materials that can be in recycle contains many categories which is glass, paper, metal, plastic, textile and electronic. Not all the thrashers could be recycle such as bottle , junk food, plastic but these item could be throw in the right way follow by the category of the dustbin. The materials will in recycle whether or not to bring at disposal trash place, collect from street and been arranged, It has been cleaned and processed to the new materials. The materials in recycle will be in the categorized before it will be cleaned, then the material will be processed beginning made new products and recycle can save the environment. Effort to practice people to join a recycle activities is not yet in a good plan and achieve the best way because not at all is not aware to the recycle campaign. The results of this study found that PPSPPA percentage of people in this country has abilities to do re-cycle is still on stage that's great to see not only as much as 40 percent to 45 percent only. In induced failure consciousness to Malaysia over the people that they may because pollution problems waste increasingly widespread and it is difficult to restrain.